2014
DOI: 10.1093/annhyg/meu076
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation of Carbon Monoxide from a Biomass Pellet Storage Tank—A Study of the Effects of Variation of Temperature and Cross-ventilation on the Efficiency of Natural Ventilation

Abstract: Wood pellets have been reported to emit toxic gaseous emissions during transport and storage. Carbon monoxide (CO) emission, due to the high toxicity of the gas and the possibility of it being present at high levels, is the most imminent threat to be considered before entering a pellet storage facility. For small-scale (<30 tons storage capacity) residential pellet storage facilities, ventilation, preferably natural ventilation utilizing already existing openings, has become the most favored solution to overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Hexanal odor and sensory irritation levels were exceeded, suggesting the need of improving ventilation in store rooms to mitigate short-term impacts of aldehydes coming from stored wood pellets. As recommended by earlies studies, the use of natural ventilation, such as windows, fans, tubes that connect the store room with the outside air 34 can reduce the concentration of these VOCs. Extensive further study is needed of the effects of temperature, cross-ventilation, type of storage, room volume, and pellet age so that they can be taken into account in developing recommendations of a storage room design and proper ventilation in domestic and commercial buildings using pellet boilers.…”
Section: Discussionmentioning
confidence: 99%
“…Hexanal odor and sensory irritation levels were exceeded, suggesting the need of improving ventilation in store rooms to mitigate short-term impacts of aldehydes coming from stored wood pellets. As recommended by earlies studies, the use of natural ventilation, such as windows, fans, tubes that connect the store room with the outside air 34 can reduce the concentration of these VOCs. Extensive further study is needed of the effects of temperature, cross-ventilation, type of storage, room volume, and pellet age so that they can be taken into account in developing recommendations of a storage room design and proper ventilation in domestic and commercial buildings using pellet boilers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inclusion of ventilation to reduce carbon monoxide has now been recognised by the industry in Central Europe. [12] …”
Section: Methodsmentioning
confidence: 99%
“…Brožek (2013) concluded that pellets should be stored in closed plastic bags to eliminate or minimize air and moisture diffusion. Variations in pellet size, density, and mc may be quick ways to determine the quality of a storage method, however, factors such as toxic gas accumulation should be monitored before entering a pellet storage facility with no or low levels of ventilation (Emhofer et al 2014).…”
Section: Storage and Handlingmentioning
confidence: 99%
“…The danger of gaseous emissions has only been recently addressed after several fatalities involving CO poisoning (Alakoski et al 2016). The revelation of this risk has resulted in the need to retrofit many non-ventilated residential pellet store rooms in Europe, where toxic or fatal CO levels often accumulate (Emhofer et al 2014). Alakoski et al (2016) conducted a short review on the gaseous emissions of pellets, with the following findings.…”
Section: Storage and Handlingmentioning
confidence: 99%